2017
DOI: 10.1136/bmjopen-2017-016045
|View full text |Cite
|
Sign up to set email alerts
|

Adverse childhood or adult experiences and risk of bilateral oophorectomy: a population-based case–control study

Abstract: ObjectivesBilateral oophorectomy has commonly been performed in conjunction with hysterectomy even in women without a clear ovarian indication; however, oophorectomy may have long-term deleterious consequences. To better understand this surgical practice from the woman’s perspective, we studied the possible association of adverse childhood or adult experiences with the subsequent occurrence of bilateral oophorectomy.DesignPopulation-based case–control study.SettingOlmsted County, Minnesota (USA).ParticipantsFr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 43 publications
4
21
0
Order By: Relevance
“…In women who underwent the oophorectomy before age 40 years, we also observed a strong association with prior physical abuse experienced during adulthood. 22 23 …”
Section: Findings To Datementioning
confidence: 99%
See 2 more Smart Citations
“…In women who underwent the oophorectomy before age 40 years, we also observed a strong association with prior physical abuse experienced during adulthood. 22 23 …”
Section: Findings To Datementioning
confidence: 99%
“…Because of the recent findings from our case–control study linking bilateral oophorectomy to adverse childhood or adult experiences in a subsample of MOA-2, we plan to expand the medical record abstraction for these variables to all women in the cohort. 22 23 We plan to include adverse childhood or adult experiences as possible confounding or effect modifying variables in future analyses.…”
Section: Findings To Datementioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies in the United States [6], and around the world [10], have not reported a significant sex difference. Different theories for the geographical difference in the prevalence and incidence of AD by sex between the United States and Europe have been suggested [6, 13]. For example, in the early part of the 20 th century, gender differences in educational and occupational opportunities varied between the United States and Europe.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Such experiences are associated with infertility, low birth weight, and early bilateral oophorectomy for noncancerous conditions. [10][11][12] Additionally, women Veterans may have experiences and exposures unique to military service that could adversely impact their reproductive health, including environmental and occupational exposures, military sexual assault, and combat-associated injuries. Possibly related to these exposures, women Veterans have a higher prevalence of posttraumatic stress disorder (PTSD) than their non-Veteran peers.…”
Section: Introductionmentioning
confidence: 99%